Pengaruh Model Pembelajaran dan Gaya Berpikir Terhadap Hasil Belajar Mata Kuliah Filsafat Pendidikan - Hamlan Andi Baso Malla; Herlina Herlina; Misnah Misnah (Jurnal Teknologi Pendidikan)
This study aims at revealling the effect of instructional models and students thinking styles on the students learning outcomes of the educational philosophy course at the IAIN Palu. The research method used in this research was quasi experiment with a 2 x 2 factorial design, data were analyzed statistically using ANAVA. The result of research shows that 1) the students learning outcomes who learned through deep learning model is higher than the students who learned through surface learning; 2) there is an interaction effect between instructional model with thinking style on the learning outcomes of educational philosophy course; 3) student learning outcomes using deep learning model and have divergent thinking style is higher than student learning outcomes that have convergent thinking style; 4) student learning outcomes using surface learning model and have the convergent thinking style is higher than student learning outcomes that have divergent thinking style.